2020
DOI: 10.1002/bmc.4829
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chemical constituents and six compounds in Qu‐feng‐sheng‐shi Granules via HPLC–ESI–Q/TOF–MSn and HPLC–UV technique

Abstract: Qu‐feng‐sheng‐shi Granules (QFSSG), a common prescription for the treatment of chronic inflammation and allergic rhinitis, is widely used in the clinic as a traditional Chinese medicine. Chemical analysis and quality control studies of this formulation are relatively limited compared with pharmacological studies. In this study, a high‐performance liquid chromatography coupled with electrospray ionization quadrupole time‐of‐flight tandem mass spectrometry (HPLC–ESI–Q/TOF–MSn) was used to identify the components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…As the phenylpropanoids polymers, the typical characteristic ion fragments of lignans are M/2 or M/3 peak, whose response intensity is relatively high. The other cleavage rules are consistent with phenylpropanols [ 23 ]. In the mass spectrogram of secoisolariciresinol (C 20 H 26 O 6 , [M-H] − , P64), it is observed that the parent ion is m/ z 361.1683, with the daughter ion M/2–1 peak m/ z 179.0712.…”
Section: Resultssupporting
confidence: 55%
“…As the phenylpropanoids polymers, the typical characteristic ion fragments of lignans are M/2 or M/3 peak, whose response intensity is relatively high. The other cleavage rules are consistent with phenylpropanols [ 23 ]. In the mass spectrogram of secoisolariciresinol (C 20 H 26 O 6 , [M-H] − , P64), it is observed that the parent ion is m/ z 361.1683, with the daughter ion M/2–1 peak m/ z 179.0712.…”
Section: Resultssupporting
confidence: 55%